2016
DOI: 10.5603/gp.2016.0047
|View full text |Cite
|
Sign up to set email alerts
|

Posture and low back pain during pregnancy — 3D study

Abstract: Objectives: Back pain is a common complaint of pregnant women. The posture, curvatures of the spine and the center of gravity changes are considered as the mechanisms leading to pain. The study aimed to assess spinal curvatures and static postural characteristics with three-dimensional surface topography and search for relationships with the occurrence of back pain complaints among pregnant women. Material and methods:The study was conducted from December 2012 to February 2014. Patients referred from Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
2
14
0
5
Order By: Relevance
“…All participants with LPP complaints reported some level of disability (minimal, moderate or severe) detected by this instrument. The majority of pregnant women reported minimal and moderate disability, as observed in the studies by Madeira et al (2013) and Sousa et al [12,15]. Although the participants in this study did not report complete inability to perform daily activities to the detriment of the LPP complaint, some level of partial and temporary limitations were found in pregnant women.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…All participants with LPP complaints reported some level of disability (minimal, moderate or severe) detected by this instrument. The majority of pregnant women reported minimal and moderate disability, as observed in the studies by Madeira et al (2013) and Sousa et al [12,15]. Although the participants in this study did not report complete inability to perform daily activities to the detriment of the LPP complaint, some level of partial and temporary limitations were found in pregnant women.…”
Section: Discussionsupporting
confidence: 51%
“…In this context, lumbopelvic pain (LPP) represents a major problem often faced by many pregnant women [13]. Previous studies report that pain complaints may be of sufficient intensity and duration to affect the quality of life of the pregnant woman, able to interfere in performing daily activities such as sit-to-stand and walking, in addition to compromising their performance at work [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Betsch et al [25] found that there was no change in lordotic angle during pregnancy but an increase in kyphosis was observed both in the developing pregnancy and when comparing pregnancy results to postpartum results. Another study observed no changes in either kyphosis or lordosis angles throughout pregnancy [26]. Across these studies, there is an obvious conflict between findings, while some participants show deviations from the overall findings.…”
Section: Spinal Curvaturementioning
confidence: 93%
“…Several studies also assess the association of spinal curvature with pain levels in pregnancy [21,22,[24][25][26]34], reporting that levels of low back pain increase with the developing pregnancy [4]. It is concluded that 95% of participants experienced LBP, which correlates with increased lordosis [24].…”
Section: Spinal Curvaturementioning
confidence: 99%